(untitled) (Вісник Київського національного університету імені Тараса Шевченка. Хімія, 2007)
The peculiarities of the exchange interactions between copper(ll) atoms are considered for the case of poly- and heteropolynuclear complexes. EPR-spectroscopy has been shown to have advantages for the investigation of weak spin-spin interactions.